Where Dopaminergic and Cholinergic Systems Interact: A Gateway for Tuning Neurodegenerative Disorders - Amalric, Marianne; Pattij, Tommy; Sotiropoulos, Ioannis; Silva, Joana M.; Sousa, Nuno; Ztaou, Samira; Chiamulera, Cristiano; Wahlberg, Lars U.; Emerich, Dwaine F.; Paolone, Giovanna (Frontiers in Behavioral Neuroscience, 2021)
Historically, many investigations into neurodegenerative diseases have focused on alterations in specific neuronal populations such as, for example, the loss of midbrain dopaminergic neurons in Parkinson’s disease (PD) and loss of cholinergic transmission in Alzheimer’s disease (AD). However, it has become increasingly clear that mammalian brain activities, from executive and motor functioning to memory and emotional responses, are strictly regulated by the integrity of multiple interdependent neuronal circuits. Among subcortical structures, the dopaminergic nigrostriatal and mesolimbic pathways as well as cholinergic innervation from basal forebrain and brainstem, play pivotal roles in orchestrating cognitive and non-cognitive symptoms in PD and AD. Understanding the functional interactions of these circuits and the consequent neurological changes that occur during degeneration provides new opportunities to understand the fundamental inter-workings of the human brain as well as develop new potential treatments for patients with dysfunctional neuronal circuits. Here, excerpted from a session of the European Behavioral Pharmacology Society meeting (Braga, Portugal, August 2019), we provide an update on our recent work in behavioral and cellular neuroscience that primarily focuses on interactions between cholinergic and dopaminergic systems in PD models, as well as stress in AD. These brief discussions include descriptions of (1) striatal cholinergic interneurons (CINs) and PD, (2) dopaminergic and cholinergic modulation of impulse control, and (3) the use of an implantable cell-based system for drug delivery directly the into brain and (4) the mechanisms through which day life stress, a risk factor for AD, damage protein and RNA homeostasis leading to AD neuronal malfunction.